Improving the quality and productivity of palm oil through mechanisation in palm oil companies - Maisarah, Ismail; Nur Sofia Nabila, Alimin; Bathaei, Ahmad (Penerbit Universiti Malaysia Pahang, 2024)
The purpose of this study is to enhance palm oil productivity and quality through mechanisation by identifying palm oil production processes and recommending appropriate mechanisation strategies to increase palm oil productivity and quality. The data was gathered via semi-structured interviews with employees from YP Plantation Holdings Sdn Bhd. The findings hope to offer recommendations for YPPH to optimise the production process, improve palm oil quality, and increase productivity. This will not only uphold YPPH's market competitiveness but also promote better farmer welfare, expand the agricultural industry, and influence policy and decision-making. The study also offers a conclusion and discussion, research recommendations, identification of literary gaps, and best practices for future development. Implementing the proposed solutions can lead to improved palm oil quality, higher output, and overall growth for YPPH and the agricultural sector, notably the palm oil industry. This will help YPPH to improve palm oil quality while increasing output and overall development, solidifying its position as a vital player in the palm oil market.